Neuroinflammation modifies the relationship between stress and perivascular spaces in an elderly population with different levels of cognitive impairment - Sibilia, Francesca; Sheikh-Bahaei, Nasim; Mack, Wendy J.; Barisano, Giuseppe; Choupan, Jeiran (Frontiers in Cellular Neuroscience, 2024)
Background: Perivascular spaces (PVS) are fluid-filled spaces surrounding the brain parenchymal vasculature. Literature suggests that PVS may play a significant role in aging and neurological disorders, including Alzheimer's disease (AD). The aim of this study is to investigate whether the relationship between MRI-visible PVS and stress is influenced by neuroinflammation in an elderly population with different levels of cognitive impairment.Methods: Using brain MRI scans acquired at 1.5T, PVS were quantified in a cohort of 461 individuals, consisting of cognitively healthy controls (n=48), people with mild cognitive impairment (MCI, n=322) and Alzheimer's disease (AD, n=91). PVS volume fraction was calculated in the basal ganglia and centrum semiovale using a semiautomated segmentation approach. Stress was quantified with levels of salivary cortisol.Inflammatory biomarkers measured from plasma included cytokines, matrix metalloproteinases and C-reactive protein. General linear models were used to test the relationship between PVS and cortisol, when interacting with inflammatory markers. This was done on the whole cohort and within each clinical cognitive group.Results: In the centrum semiovale, higher inflammation levels reduced the relationship of cortisol with PVS. In basal ganglia, higher levels of C-reactive protein reduced the negative relationship of cortisol with PVS. All analyses were accounted for age, sex, body mass index (BMI) and total hippocampal volume. There was a significant interaction effect between cortisol and C-reactive protein on PVS volume fraction in the MCI group.Discussion: These findings suggest an influence of neuroinflammation on the PVS structure in Alzheimer's disease spectrum, and offer insight for better understanding physiological processes of cognitive impairment onset.